The Research Compendium : Review and Abstracts of Graduate Research, 1942-1962 - Avison, Margaret, 1918-2007 (Book collections on Project MUSE., 1964)
This book represents an important contribution by the School of Social Work at the University of Toronto. It is a record of a carefully designed plan to include a worthwhile research experience in the educational programme of every student engaged in graduate education for the profession.